THE PROBLEM OF INTERFERENCE. WAYS OF PREVENTING AN OVERCOMING IT - Abduraxmanova Zilola Yoqubjon qizi; Nurmamatova Mashhura Xolmurod qizi (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This article explores the multifaceted issue of interference, delving into its diverse forms across communication systems, technology, and human interactions. It identifies and categorizes types of interference—physical, psychological, and environmental—while proposing comprehensive solutions to prevent and overcome these challenges. The piece provides insight into technological solutions such as frequency management and shielding, offering ways to mitigate signal disruption in communication systems. It also addresses strategies for human interactions, emphasizing the importance of active listening, clear communication, and conflict resolution techniques in overcoming psychological interference.